Novel GLRA1 missense mutation (P250T) in dominant hyperekplexia defines an intracellular determinant of glycine receptor channel gating - Saul, Brigitta; Kuner, Thomas; Sobetzko, Diana; Brune, Wolfram; Hanefeld, Folker; Meinck, Hans-Michael; Becker, Cord-Michael (The journal of neuroscience, 1999)
Missense mutations as well as a null allele of the human glycine receptor α1 subunit gene GLRA1 result in the neurological disorder hyperekplexia [startle disease, stiff baby syndrome, Mendelian Inheritance in Man (MIM) #149400]. In a pedigree showing dominant transmission of hyperekplexia, we identified a novel point mutation C1128A of GLRA1. This mutation encodes an amino acid substitution (P250T) in the cytoplasmic loop linking transmembrane regions M1 and M2 of the mature α1 polypeptide. After recombinant expression, homomeric α1P250T subunit channels showed a strong reduction of maximum whole-cell chloride currents and an altered desensitization, consistent with a prolonged recovery from desensitization. Apparent glycine binding was less affected, yielding an approximately fivefold increase inKi values. Topological analysis predicts that the substitution of proline 250 leads to the loss of an angular polypeptide structure, thereby destabilizing open channel conformations. Thus, the novel GLRA1 mutant allele P250T defines an intracellular determinant of glycine receptor channel gating.